BPJS Health Service Quality Audit Using Cobit 5.0 on Domain Deliver, Service and Support at Ciluluk Health Center - Encep Supriatna; Sonya Fitriani; Bimbim Yosef Suhendar (Research Collaboration Community (RCC), 2023)
Ciluluk Community Health Center is a community health service center in Cikancung District, Bandung Regency. In its operations, it cooperates with the Social Security Administration Agency (BPJS). In 2021 there was a decrease in the number of BPJS participants by 14.2% which had an impact on the capitation of the Ciluluk Health Center which had decreased by 9.73%. This research was conducted to audit the quality of BPJS Health services at the Ciluluk Public Health Center, Cikancung District, Bandung Regency using the COBIT 5.0 domain Deliver, Service and support method. Work Operational Process is at level 1 with a value of 87%, Action Service Process, is at level 2 with a value of 90%, Problem Handling Process, is at level 5 with a value of 100%, Process of Providing Directions, is at level 5, with a value of 99 %, Information System Service Process, is at level 3, with a value of 79.33%, Controlling Process, is at level 3 with a value of 96.25%. Thus COBIT 5.0 domain Deliver, Service and support can help evaluate the quality of service at the Ciluluk Health Center. acronyms.